Tumor suppressor miR-29c regulates radioresistance in lung cancer cells - Elena Arechaga-Ocampo; Cesar Lopez-Camarillo; Nicolas Villegas-Sepulveda; Claudia H Gonzalez-De la Rosa; Isidro X Perez-Añorve; Reynalda Roldan-Perez; Ali Flores-Perez; Omar Peña-Curiel; Oscar Angeles-Zaragoza; Rosalva Rangel Corona; Juan A Gonzalez-Barrios; Raul Bonilla-Moreno; et al. (Tumor Biology)
Radiotherapy is an important treatment option for non-small cell lung carcinoma patients. Despite the appropriate use of radiotherapy, radioresistance is a biological behavior of cancer cells that limits the efficacy of this treatment. Deregulation of microRNAs contributes to the molecular mechanism underlying resistance to radiotherapy in cancer cells. Although the functional roles of microRNAs have been well described in lung cancer, their functional roles in radioresistance are largely unclear. In this study, we established a non-small cell lung carcinoma Calu-1 radioresistant cell line by continuous exposure to therapeutic doses of ionizing radiation as a model to investigate radioresistance-associated microRNAs. Our data show that 50 microRNAs were differentially expressed in Calu-1 radioresistant cells (16 upregulated and 34 downregulated); furthermore, well-known and novel microRNAs associated with resistance to radiotherapy were identified. Gene ontology and enrichment analysis indicated that modulated microRNAs might regulate signal transduction, cell survival, and apoptosis. Accordingly, Calu-1 radioresistant cells were refractory to radiation by increasing cell survival and reducing the apoptotic response. Among deregulated microRNAs, miR-29c was significantly suppressed. Reestablishment of miR-29c expression in Calu-1 radioresistant cells overcomes the radioresistance through the activation of apoptosis and downregulation of Bcl-2 and Mcl-1 target genes. Analysis of The Cancer Genome Atlas revealed that miR-29c is also suppressed in tumor samples of non-small cell lung carcinoma patients. Notably, we found that low miR-29c levels correlated with shorter relapse-free survival of non-small cell lung carcinoma patients treated with radiotherapy. Together, these results indicate a new role of miR-29c in radioresistance, highlighting their potential as a novel biomarker for outcomes of radiotherapy in lung cancer.